2019
DOI: 10.1111/evo.13704
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization and introgression during density‐dependent range expansion: European wildcats as a case study

Abstract: Interbreeding between historically allopatric species with incomplete reproductive barriers may result when species expand their range. The genetic consequences of such hybridization depend critically on the dynamics of the range expansion. Hybridization models during range expansion have been developed but assume dispersal to be independent from neighboring population densities. However, organisms may disperse because they are attracted by conspecifics or because they prefer depopulated areas. Here, through s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 68 publications
(91 reference statements)
3
32
0
Order By: Relevance
“…armigera. This pattern is in agreement with theoretical models of secondary contact after invasions that account for demographic processes, which predict greater introgression of neutral genes from the local into the foreign species (Currat et al 2008;Mesgaran et al 2016;Quilodrán et al 2019). This asymmetry is partly explained by a demographic imbalance between the two species at the wave front, where the invading species is at lower densities (Currat et al 2008;Hall 2016;Mesgaran et al 2016).…”
Section: Asymmetric Introgression At the Front Of An Invasionsupporting
confidence: 87%
“…armigera. This pattern is in agreement with theoretical models of secondary contact after invasions that account for demographic processes, which predict greater introgression of neutral genes from the local into the foreign species (Currat et al 2008;Mesgaran et al 2016;Quilodrán et al 2019). This asymmetry is partly explained by a demographic imbalance between the two species at the wave front, where the invading species is at lower densities (Currat et al 2008;Hall 2016;Mesgaran et al 2016).…”
Section: Asymmetric Introgression At the Front Of An Invasionsupporting
confidence: 87%
“…Empirical evidence is provided by gulls and mice (Table ). A difficulty with this approach is that it is not straightforward to determine when secondary contact was established and hence how long the hybrid zone has been on the move, and that the signal soon disappears after a zone stops moving (Gay, Crochet, Bell, & Lenormand, ; Wang et al., ).Introgression across a moving hybrid zone is predicted to be asymmetric, as selectively neutral alleles from the displaced population introgress into the expanding one, in the wake of a moving hybrid zone (Currat, Ruedi, Petit, & Excoffier, ; Quilodrán, Nussberger, Montoya‐Burgos, & Currat, ). Introgression of a single marker such as mitochondrial DNA could be (and regularly has been) interpreted as resulting from hybrid zone movement (Buggs, ), but excluding other potential causes for introgression of single markers is not straightforward (Dasmahapatra et al., ; Toews & Brelsford, ), making such data insufficient to infer historical hybrid zone movement.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Introgression across a moving hybrid zone is predicted to be asymmetric, as selectively neutral alleles from the displaced population introgress into the expanding one, in the wake of a moving hybrid zone (Currat, Ruedi, Petit, & Excoffier, 2008;Quilodrán, Nussberger, Montoya-Burgos, & Currat, 2019). Introgression of a single marker such as mitochondrial DNA could be (and regularly has been) interpreted as resulting from hybrid zone movement (Buggs, 2007), but excluding other potential causes for introgression of single markers is not straightforward (Dasmahapatra et al, 2002;Toews & Brelsford, 2012), making such data insufficient to infer historical hybrid zone movement.…”
Section: Text Box Inferring Historical Hybrid Zone Movementmentioning
confidence: 99%
“…To assess the expected levels of the introgression of domestic genes into wildcats, we performed spatially explicit simulations of the well-documented case of wildcat demographic recovery in the Swiss Jura Mountains (Nussberger, Greminger, Grossen, Keller, & Wandeler, 2013;Nussberger et al, 2007Nussberger et al, , 2014. We used demographic parameter values and observed introgression based on previously published studies simulating the hybridization between the two types of cats (Nussberger et al, 2018;Quilodrán et al, 2019), as shown in Table 1.…”
Section: Implementation On Wildcatsmentioning
confidence: 99%
“…However, competition for environmental resources has been suggested to be important, with wildcats potentially presenting an advantage after antagonistic encounters (Gil-Sánchez, Jaramillo, & Barea-Azcón, 2015). Here, we thus include competition between TA B L E 1 Observed introgression and parameter values used to simulate interbreeding between European wildcats and domestic cats (modified from Quilodrán et al (2019) and Nussberger et al (2018) the two types of cats. We also use an approximate Bayesian computation method to better estimate the value of interbreeding, instead of the non-linear regression method used in the previous approach (Nussberger et al, 2018;Quilodrán et al, 2019).…”
Section: Introductionmentioning
confidence: 99%